How do students assess the impact of integrating digital technologies on the mathematics classroom? - Gurevich, Irina; Barchilon Ben-Av, Mercedes (International journal of mathematical education in science and technology, 2023)
The current research sought to test the effect of using technology on students in various mathematics courses. The study was conducted in the mathematics department of our college of education. We tested how the students evaluate our teaching method and how involved they are in the acquisition of knowledge while using different digital applications with respect to the basic features of the traditional compared to the constructivist classroom. We compared the students' attitudes towards the role of digital technology integration in learning/teaching mathematics in different courses taught with and without technological tools. The results indicate that the students' attitude towards teaching mathematics with the use of technology correspond with the constructivist approach to teaching, while their assessment of the classes without the use of technology matches characteristics of traditional classroom. The obtained result aligns well with the notion that integration of technology in mathematics teaching makes it possible to achieve a qualitatively higher level of teaching this subject at school.